Barriopsis tectonae sp. nov. a new species of Botryosphaeriaceae from Tectona grandis (teak) in Thailand - Doilom, Mingkwan; Shuttleworth, Lucas A.; Roux, Jolanda; Chukeatirote, Ekachai; Kevin, Hyde D. (Phytotaxa, 2014)
Tectona grandis (teak) is an increasingly important timber resource globally. It is native to Asia, including Thailand. In this paper a new species of Barriopsis, B. tectonae sp. nov., is described from a dead T. grandis branch collected in Thailand. Barriopsis tectonae can be differentiated from the two previously described species of Barriopsis; B. fusca and B. iraniana, by its ascospore and conidial dimensions. Phylogenetic evaluation of the ITS, TEF1-α and BT genomic regions provide further evidence that B. tectonae is a novel species.